Development of Administration Quality In Madrasah Tsanawiyah‘Aisyiyah, Medan - Deliati Deliati; Nur Sakinah; Nadlra Naimi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Partners in this research are Madrasah Tsanawiyah Swasta‘Aisyiyah Pasar Merah and Madrasah Tsnawiyah Swasta Islamiyah Belawan. The existence of schools ‘Aisyiyah is equipped with school administration as a means of supporting learning resources and student learning success. As one source of learning in schools, administration helps achieve school quality improvement. Considering the importance of school administration, it is necessary to have a neatly arranged management effectively and efficiently so that the high quality administration functions of the school in order to improve school accreditation can really be realized. The purpose of the administration of Madrasah Tsanawiyah is to advance a school if the administration is neatly arranged and systematic so that it can improve the quality of schools and principals and students. Management of Administration in Madrasah Tsanawiyah Swasta‘Aisyiyah is still inadequate, as stated in Article 35 paragraph (2) Government Regulation Number 19 of 2005 concerning National Education Standards needs to stipulate Minister of National Education Regulation on School / Madrasah Administrative Standards. However, the problems found were not a few school administrations whose management was not professional. This is due to the understanding that the school administration still does not understand about managing the school administration properly. The target to be achieved through this PKPM activity is the development of school administration management for Madrasah Tsanawiyah Swasta ‘Aisyiyah which is effective and efficient. Implementation methods carried out (1) Preparation of deliberations with partners, PWA Majelis Didasmen Wilayah and Madrasah Tsanawiyah Swasta‘Aisyiyah (2) Implementation (actions) fostering management of school administration' Aisyiyah, (3) Observation of management of school administration 'Aisyiyah, (4) Evaluation The Administration Management Development Checklist, and (5) Reflections on Administratio of Madrasah Tsanawiyah Swasta‘Aisyiyah.